Lean knowledge management : how NASA implemented a practical KM program - Forsgren, Roger (Portfolio and project management collection., 2021)
NASA suffered three human spaceflight tragedies and Lean Knowledge Management was a major tool that helped NASA management implement massive cultural changes. Traditional knowledge management is too often regarded as overly complicated or a wasteful bureaucratic exercise, but Lean Knowledge Management can become a critical component for your organization to operate effectively, efficiently and safely. Lean Knowledge Management simplifies the process by: Clearly defining your organization's key employees; Filtering the enormous amount of internal "information" into "critical knowledge"; Utilizing a myriad of resources to get this critical knowledge to the people who need it most - the very people that can make your organization successful. Repetitive mistakes and failures can cost an organization millions of dollars in lost revenue, scrap, and even lawsuits. Lean Knowledge Management strips away the academic jargon and implements a practical, cost-effective, organic program emphasizing lessons of the past.